Analisa Bauran Pemasaran Yang Mempengaruhi Keputusan Pembelian Baju di Beberapa Departement Store di Kota Malang - Tria Warsa Enggal; Mochamad Bukhori; Dwiyani Sudaryanti (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2019)
Abstract This study aimed to investigate the effect between the marketing mix components; Products (X1), Price (X2), Promotion (X3), and Place (X4) on the Buying decision (Y) of clothing consumers at the selected department stores in Malang City. The population in this study was all the clothing consumers at the selected department stores in Malang City. Sampling was done by Proportional random sampling technique, and obtained the sample of 150 respondents. Primary data was collected using questionnaire as the research instrument. Data analysis was performed using Multiple Linear Regression analysis on the SPSS 21 program. The results validated that Products (X1), Price (X2), Promotion (X3), and Place (X4) have a significant effect on the consumers’ buying decision (Y). This is showed by the significance value (p-value) < α (0.05) both in partial and simultaneous test. The influence of all components of the marketing mix on the consumers’ buying decision is 50.3% (R square 0.503). In addition, the component of marketing mix with the biggest influence is promotion (Standardized coefficient 0.334). Therefore, it can be concluded that the marketing mix has a significant effect on the buying decision of clothing consumers of department stores in Malang City.